Characterization of Arsenic-Resistant Endophytic Bacteria From Alfalfa and Chickpea Plants - Tashan, Hazhir; Harighi, Behrouz; Rostamzadeh, Jalal; Azizi, Abdolbaset (Frontiers in Plant Science, 2021)
The present investigation was carried out to isolate arsenic (As) resistant endophytic bacteria from the roots of alfalfa and chickpea plants grown in arsenic-contamination soil, characterize their As tolerance ability, plant growth-promoting characteristics, and their role to induce As resistance by the plant. A total of 4 root endophytic bacteria were isolated from plants grown in As contaminated soil (160- 260 mg As kg1 of soil). These isolates were studied for plant growth-promoting (PGP) characteristics through siderophore, phosphate solubilization, nitrogen fixation, protease and lipase production, and presence of arsenate reductase (arsC) gene. Based on 16S rDNA sequence analysis, these isolates belong to the genera Acinetobacter, Pseudomonas, and Rahnella. All isolates were found As tolerant, of which one isolate, Pseudomonas sp. QNC1 showed the highest tolerance up to 350 mM concentration in the LB medium. All isolates exhibited phosphate solubilization activity. Siderophore production activity was shown by only Pseudomonas sp. QNC1 while nitrogen fixation activity was shown by only Rahnella sp. QNC2 isolate. Acinetobacter sp. QNA1, QNA2 and Rahnella sp. QNC2 exhibited lipase production while only Pseudomonas sp. QNC1 was able to produce protease. The presence of the arsC gene was detected in all isolates. The effect of endophytic bacteria on biomass production of alfalfa and chickpea in five levels of arsenic concentrations (0. 10, 50, 75, and 100 mg/kg soil) was evaluated. The fresh and dry weight of roots of alfalfa and chickpea plants were decreased as the arsenic concentration of the soil was increased. Results indicate that the fresh and dry root weight of alfalfa and chickpea plants were significantly higher in endophytic bacteria-treated plants compared to non-treated plants. Inoculation of chickpea plants with Pseudomonas sp. QNC1 and Rahnella sp. QNC2 induced lower NPR3 gene expression in chickpea roots grown in soil with the final concentration of 100 mg/kg sodium arsenate compared with the non-endophyte-treated control. The same results were obtained in Acinetobacter sp. QNA2-treated alfalfa plants grown in the soil plus 50 mg/kg sodium arsenate. These results demonstrated that arsenic-resistant endophytic bacteria are potential candidates to enhance plant growth promotion in As contamination soils.